Mentari Jewellery / Mohd Naim Abd Wahab ... [et al.] - Abd Wahab, Mohd Naim; Mohamad, Zaidi; Sabarudin, Shahrenn; Abd.Manan, Ahmad Shawaludin; Mohd Suhaim, Mohamad Syahrir (Faculty of Civil Engineering, 2003)
Mentari Jewellery Enterprise is a Company folly owned by Bumiputra. A total capital of RM145,727.00 has been invested in this business. The amount of financial assistance is RM99,416.00 from Perwira Affin Bank. We are sure that this Company will successfully achieve our vision.